2017
DOI: 10.37134/jsspj.vol6.1.1.2017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combined self-talk, imagery and video-modelling interventions on anaerobic performance, heart rate response and self-efficacy

Abstract: The aim of this study was to investigate the effects of instructional and motivational self-talk combine with imagery and video-modelling interventions on anaerobic performance, heart rate response and self-efficacy. Forty-five active male participants were recruited in this study as they passed the screening test of Sport Imagery Ability Measure (SIAM) and scored between moderate and high. All the participants were randomly assigned into 3 groups, namely instructional group (n=15), motivational group (n=15) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This is a major psychological-related problem that has been identified as causing inconsistent performance of archery athletes during competitions. Nevertheless, according to a study conducted [18], [19], [20], a combination of mental and physical training is better if athletes practice it often as opposed to just practicing physical training alone.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major psychological-related problem that has been identified as causing inconsistent performance of archery athletes during competitions. Nevertheless, according to a study conducted [18], [19], [20], a combination of mental and physical training is better if athletes practice it often as opposed to just practicing physical training alone.…”
Section: Problem Statementmentioning
confidence: 99%
“…The reliability of the Sport Imagery Ability Measure (SIAM) questionnaire has been reported in previous study [21] and is found to be reliable. The questionnaire was translated into the Malay language [20] with the Cronbach alpha reliability coefficient of r = 0.80. In addition, translated Belief in Self-talk Questionnaire (BSQ) [22] [23] was used to assess belief in the effectiveness of self-talk.…”
Section: Instrumentationmentioning
confidence: 99%